Bi vacancy formation in BiFeO3 epitaxial thin films under compressive (001)-strain from first principles. Issue 16 (8th April 2019) - Xia, Lu; Tybell, Thomas; Selbach, Sverre M.
Abstract : Bi vacancy formation upon epitaxial (001)-strain in BiFeO3 was investigated by Density Functional Theory (DFT) calculations. Abstract : Point defects in BiFeO3 affect both structural and functional properties. To elucidate the role of single Bi vacancies and Bi–O vacancy pairs we investigate their stability and effect on structural and ferroelectric properties in BiFeO3 using first principles density functional theory calculations. Compressive strain is shown to stabilize Bi vacancies, and the Bi vacancy enthalpy of formation drops abruptly at the structural transition from rhombohedral R-phase to tetragonal T-phase. For Bi–O vacancy pairs the situation is more complex, albeit stabilization is found under compressive strain. Out-of-plane oriented vacancy pairs are stabilized in the T-phase, while in-plane oriented vacancy pairs are destabilized compared to the R-phase. It is shown that single Bi vacancies do not affect the spontaneous polarization, while in-plane Bi–O vacancy pairs reduce the in-plane component of the polarization, resulting in a polarization rotation towards [001]. We also discuss the effect of vacancies on the electronic properties of BiFeO3, and show that Bi deficiency is consistent with the experimentally reported p-type conductivity.